2003
DOI: 10.1046/j.1365-3148.2003.00458.x
|View full text |Cite
|
Sign up to set email alerts
|

Haemolytic disease of the newborn due to maternal irregular antibodies in the Chinese population in Taiwan

Abstract: From 1991 to 2000, amongst 23,886 full-term healthy Chinese babies delivered at our hospital, 2615 babies developed neonatal hyperbilirubinaemia. After excluding other causes of hyperbilirubinaemia and identifying the irregular antibodies, 15 cases of haemolytic disease of the newborn (HDN) due to maternal irregular antibodies were diagnosed; three cases were born in our hospital and 12 cases were referred. Amongst these 15 babies, six cases had HDN due to anti-E, three cases due to anti-E + c, three cases due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 12 publications
(15 reference statements)
4
41
0
2
Order By: Relevance
“…20 Britain. 21 21 22 Sallander et al 23 Bojadzieva et al 24 Makroo et al 25 Myhre et al 26 Richard et al 27 Winters et al 28 Giblett et al 29 Tormey et al 30 Zhu et al 31 Yeela et al 32 Garcia et al 33 Andersen et al 34 Wu et al 35 Varghese et al 36 Jeremiah et al 37 Healthy …”
Section: Resultsmentioning
confidence: 99%
“…20 Britain. 21 21 22 Sallander et al 23 Bojadzieva et al 24 Makroo et al 25 Myhre et al 26 Richard et al 27 Winters et al 28 Giblett et al 29 Tormey et al 30 Zhu et al 31 Yeela et al 32 Garcia et al 33 Andersen et al 34 Wu et al 35 Varghese et al 36 Jeremiah et al 37 Healthy …”
Section: Resultsmentioning
confidence: 99%
“…In some countries, despite the low frequency, non-anti-D-erythrocyte alloimmunisation screening is recommended for gestation because of severe hemolytic disease due to subgroup incompatibility whereas in some others, these screenings are not recommended (13,14). In our country, anti-D administration in pregnancy for Rh incompatibility is adopted as a health policy but screening for subgroup incompatibility in pregnancy is not on the agenda yet (15).…”
Section: Discussionmentioning
confidence: 99%
“…16 Similar results were obtained by Sgro et al 2,17 Other than Rh and ABO incompatibility, moderate to severe cases of neonatal jaundice attributed to other minor group antibodies has been described in Asian population in the last ten years. 18,19 Genetic studies and screening of mother for irregular antibodies were not done in the study, due to financial constraints. Further genetic studies should also be considered, in those cases where no identifiable etiology are found.…”
Section: Discussionmentioning
confidence: 99%